Anti‐HBc‐nonreactive occult hepatitis B infections with HBV genotypes B and C in vaccinated immunocompetent adults. Issue 11 (24th August 2022) - Deng, Xuelian; Guo, Xiaohan; Gu, Hongfang; Wang, Dong; Laperche, Syria; Allain, Jean‐Pierre; Zang, Liang; Candotti, Daniel
Abstract: Absence of anti‐HBc reactivity with detectable anti‐HBs was observed in blood donors with occult hepatitis B virus (HBV) infection (OBI). The prevalence and mechanisms underlying this uncommon condition were investigated over time in Chinese blood donors with OBI. Isolated anti‐HBs OBI status was identified from 466, 911 donors from Dalian, China, and monitored in follow‐up (range: 2.6–84.3 months). HBV vaccination status was documented, and infecting viral strains were characterized. Of 451 confirmed OBIs (1:1035), 43 (9.5%; 1:10, 858) had isolated anti‐HBs as only serological marker. Isolated anti‐HBs OBIs differed from anti‐HBc‐reactive OBIs by significantly younger age (median 24 years), higher HBV DNA (median: 20 IU/ml) and anti‐HBs (median 60.5 IU/L) levels, paucity of mutations in HBV Core and S proteins, and high vaccination rate (72%). Vaccinated isolated anti‐HBs OBIs ( n  = 31) differed from unvaccinated ( n  = 11) by significantly younger age (22 vs 38 years), higher anti‐HBs level at index (48% vs 9% with anti‐HBs >100 IU/L) and higher frequency of anti‐HBs immune response (44% vs 20%). Of 15 vaccinated and 5 unvaccinated OBIs follow‐up, 65% (8 vaccinated and 5 unvaccinated) became HBV DNA negative suggesting aborted recent infection, while 35% (7 vaccinated) had low persistent viraemia 2 to 65 months post index. In conclusion, isolated anti‐HBs OBI in Chinese blood donors appears associated with young, vaccinated, adults exposed to HBV who predominantly develop low level aborted infection revealed by transient HBV DNA and immune anti‐HBs response. However, a subset of individuals still experienced low but persistent viral replication whose clinical outcome remains uncertain.